Analysis Of Risk for Class Shifting And Determinants of BPJS Kesehatan Membership Using Generalized Ordered Logit-Unconstrained Partial Proportional Odds Model - Oktora, Siskarossa Ika; Wulansari, Ika Yuni; Ermawan, Geri Yesa (UI Scholars Hub, 2019)
The main source of funding of BPJS Kesehatan comes from the different premium class in which the participant registered. The medical benefits among classes are equivalent, except inpatient facilities. But when the improvement health degree is not linear with the incurred costs, problem would arise. This study aims to analyze class shifting and determinants of BPJS Kesehatan membership. Around 1.53 percent of participants access higher classes, while 5.62 percent access lower classes. Class III participants with inpatient status severity level 2 and 3, reaching 41% and 43%, respectively. In addition, 60% of non-PBI participants are Class II premium participants; most of them are male, productive age, and workers. This research using Generalized Ordered Log- it Unconstrained Partial Proportional Odds Model concludes that participants who are married tend to choose higher premium class. Whereas productive age participants and a worker is in the lower premium class. The recommendation is the evaluation of membership based on class premium contributions considering potential participants (productive age and workers) who tend should be conducted in a lower class. Although mutual assistance is the principle of National Health Insurance, specific mechanisms should be established to examine the relation of age and health status to each participant regarding the difference in the registered class, besides their economic factors